PENINGKATAN TRANSPARANSI DAN AKUNTABILITAS KEUANGAN SEKOLAH MELALUI PENGUATAN KOMPETENSI KEPALA SEKOLAH - Wardokhi, Wardokhi; Khotimah, Husnul; Agustina, Sri (Jurnal Pajak Populis, 2025)
Transparent and accountable school financial management is a fundamental prerequisite for achieving good educational governance. However, many schools still face challenges in financial recording, reporting, and accountability due to limited managerial competence of school administrators, particularly school principals. This Community Service Program (Pengabdian kepada Masyarakat) aims to enhance school principals’ competence in financial management and to improve the system of financial recording and reporting in schools. The methods employed include training, mentoring, and hands-on practice in preparing financial records and financial reports. The results indicate an improvement in principals’ understanding of financial management, better orderliness in financial recording and reporting, as well as increased transparency and accountability of school finances. This program is expected to serve as a sustainable model for strengthening school financial governance.